ANALISA YURIDIS PEKERJA DENGAN PERJANJIAN KERJA WAKTU TERTENTU (PKWT) DI PT. SOS - Rafhael Bona Riko Hesekiel (2021)
Fixed Term Work Agreement, hereinafter referred to as PKWT, is a work agreement between a worker / laborer and an entrepreneur to establish a working relationship for a certain period of time or for certain workers. The relationship between workers and companies needs each other, therefore workers and companies should not do things with arbitrarily. However, in the real practice, this is often not in line as expected because employers and workers have two opposing interests. In this normative juridical study, it was discussed that there had been injustice on the part of the company felt by one of the workers at PT. SOS whose case was brought to the Supreme Court. This paper tries to discuss how the PKWT implementation at PT. SOS if it is reviewed with the prevailing laws and regulations as well as how the legal protection that PKWT workers should be received at PT. SOS.